The Creation of the Hydrangea Multi-Styling Dress to Support the Slow Fashion Movement - Ardilla Dinullah; Feny Puspitasari (Universitas Negeri Semarang, 2026)
The fashion industry faces ongoing environmental challenges due to fast fashion practices that accelerate resource depletion and textile waste. Slow fashion has been proposed as a sustainable alternative; however, its application in Indonesia remains largely confined to zero-waste and upcycling approaches, while studies on transformative clothing are still limited. This research aims to develop the Hydrangea Multi-Styling Dress as a sustainable fashion innovation inspired by the adaptive characteristics of hydrangea flowers. Hydrangeas are employed as a biological metaphor to represent flexibility and resilience in transformative fashion design. The study adopts a practice-led research methodology through a three-stage design process consisting of concept formulation, creative exploration, and implementation. Data were analysed through systematic design documentation, development of multiple styling configurations, and expert validation involving academics and fashion practitioners. The findings indicate that the garment enables five distinct styling variations within a single product and facilitates user participation through a co-creation approach. This study contributes to the discourse on sustainable fashion by integrating transformative design, user engagement, and biological inspiration, offering an alternative pathway for advancing slow fashion practices beyond conventional strategies.